2010
DOI: 10.1161/hypertensionaha.109.147611
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Mediates Cardiac Inflammation and Fibrosis in Angiotensin II–Induced Hypertensive Cardiac Remodeling

Abstract: Abstract-Although Smad3 is a key mediator of fibrosis, the functional role of Smad3 in hypertensive cardiovascular disease remains unclear. The present study tested the hypothesis that angiotensin II may activate the transforming growth factor-␤/Smad3 pathway to mediate hypertensive cardiac remodeling in Smad3 knockout (KO) and wild-type mice by subcutaneous angiotensin II infusion and in the primary culture of Smad3 KO cardiac fibroblasts. Fourteen days after angiotensin II infusion, both Smad3 KO and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
174
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(187 citation statements)
references
References 34 publications
12
174
0
1
Order By: Relevance
“…However, the Smad3 KO mice developed less cardiac hypertrophy, fibrosis, inflammation, and dysfunction than WT mice (26). Our findings, which reflect significant cardiac hypertrophy with less elevation of blood pressure in Smad3 KO mice compared with WT mice, may reflect differences in background strain (C57BL/6 mice vs. the 129/Sv strain used in the studies reported here).…”
Section: Discussionmentioning
confidence: 51%
“…However, the Smad3 KO mice developed less cardiac hypertrophy, fibrosis, inflammation, and dysfunction than WT mice (26). Our findings, which reflect significant cardiac hypertrophy with less elevation of blood pressure in Smad3 KO mice compared with WT mice, may reflect differences in background strain (C57BL/6 mice vs. the 129/Sv strain used in the studies reported here).…”
Section: Discussionmentioning
confidence: 51%
“…Many chronic cardiovascular conditions, including valve disease and hypertension, can cause pressure overload in the ventricles that subsequently develops into hypertrophy and fibrosis (Azevedo et al, 2010;Dusenbery et al, 2014;Huang et al, 2010). Another common initiator of cardiac fibrosis is scar formation after myocardial infarction, which affects over one million Americans annually (Go, 2013).…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Deposition of de novo ECM is necessary to maintain structural integrity and requires the switch from inflammatory to profibrotic signaling factors (Frangogiannis, 2014). In both chronic and acute myocardial remodeling, AngII inhibits the degradation of collagen-1 and promotes the expression of FGF-2 and TGF-β1 that, in turn, promote cell growth and collagen production in the myocardium (Frangogiannis, 2014;Huang et al, 2010;Porter and Turner, 2009;Schuleri et al, 2012;Virag et al, 2007). TGF-β1 inhibits inflammation and promotes the differentiation of fibroblasts into MyoFBs, and the accumulation of dense ECM in the myocardial interstitium (Ikeuchi et al, 2004).…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…[2][3][4][5][6] This is supported by the findings that mice lacking Smad3 are protected against fibrosis in many disease models, including irradiative skin disorder, ischemic and hypertensive cardiac remodeling, bleomycin-induced pulmonary fibrosis, dimethylnitrosamine-induced hepatic fibrosis, and unilateral ureteral obstructive (UUO) nephropathy. [7][8][9][10][11][12] In contrast, conditional deletion of Smad2 from the kidney enhances renal fibrosis. 6 The critical role for TGF-␤/Smad signaling in fibrogenesis is further demonstrated by the finding that forced expression of Smad7 within the tissues inhibits, but loss of Smad7 promotes, fibrosis in a variety of disease models.…”
mentioning
confidence: 99%
“…Furthermore, the signaling mechanisms through which TGF-␤ 1 regulates miR-29 expression are unknown. On the basis of the known role of Smad3 in fibrosis, [2][3][4][5][6][7][8][9][10][11][12] we therefore hypothesized that miR-29 may be negatively regulated by TGF-␤/Smad3 signaling and may function as a downstream inhibitor of TGF-␤/ Smad3-mediated fibrosis. This study examined this hypothesis in cells lacking Smad3 and in a well characterized progressive renal-fibrosis mouse model of UUO nephropathy induced in Smad3 knockout (KO) mice.…”
mentioning
confidence: 99%